Stage lighting the technicians' guide : an on-the-job reference tool with online video resources - Mort, Skip (London Bloomsbury Methuen Drama, 2015)
"This practical guide covers all aspects of stage lighting, equipment, special effects lighting design and features the work of current lighting designers. The online video resources show the practical use of equipment and different lighting technique and effects."--book cover.
Includes Internet access.
Previous edition: London: Methuen Drama, 2011.
Reprinted 2023.
Includes bibliographical references and index.
Keywords: Stage lighting